Ekonomi i odling av ekologiskt potatisutsäde - Fredlund, Johan (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2004)
According to the EEG-councils regulation nr 2092/91, all seed used in organic production must have organic origin. All seed which is offered for sale must be controlled by KRAV, and also comply with the rules of the seedlegislation. The seedlegislation contains demands respecting origin, quality, growingconditions and freedom from deseases. In this piece of work I will investigate the profitability of organic potatoseedproduction, and also what it takes to produce potatoseed. The workmethod has been to, with help from counsellors and growers, make some compareable calculations for foodpotatoes and seedpotatoes, and also with help from a literaturestudy investigate which requires an organic seedcultivation must fulfil. In this piece of work I found out that the organic potatoseedproduction still is to insecure to be profitable. The attack of potatoleafmould, which is out of control, cause unequal yields and this will bring that the new EU-rules, concerning organic seed, not seems defendable yet.